Evolution of documents related to the influence of physical activity and functional capacity throughout the aging process: a bibliometric review - Cabo, Carolina A.; Hernández-Beltrán, Víctor; Gamonales, José M.; Fernandes, Orlando; Espada, Mário C.; Parraca, José A. (Frontiers in Physiology, 2024)
Physical inactivity can lead to frailty and negative health outcomes in middle-aged to older adults. Sedentary individuals have double the risk of death compared to those who engage in high levels of physical activity (PA). The advantages of practicing PA in older age are significant, with regular, moderate-intensity activity (150 min per week)being consistently linked with a decreased risk of chronic disease, cognitive decline, and mortality. Therefore, the study aimed to carry out a bibliometric review related to the terms “Physical activity,” “Functional capacity” and “Aging” including all the documents published in the Web of Science Core Collection until 31st December 2023. The sample was made up of 231 studies related to the topic. The results reported that the first document was published in 1994. However, there was no continuity in the publication of the documents till 1998, which was the first year with at least one document published. Considering 1998 as the first year, it is observed an exponential growth of 77.4%, between the oldest (1997–2008) and contemporaneous studies (2008–2023), in which “Geriatric Gerontology” was the Web of Science category with the highest number of documents (n = 59). The journal “Experimental Gerontology” was associated with the largest number of published documents (n = 7), being indexed in Quartil 2. The years 2009 had the highest number of citations (n = 1811), with a total of 7 documents published and 2018 with the higher number of documents (n = 25). These results reported the importance of PA in elderly people, and how it influences the risk of falls, improving the balance and the functional capacity. Thus, it is important to carry out programmes to promote physical activity to this population and reduce the risk of falls and the presence of diseases.